Economic Impacts of Technological Interventions in Agro Complex: A Review of Agricultural, Livestock, and Aquaculture Research - Mushaevi, Mushaevi; Nisa, Nurul (Journal of Agro Complex Development Society, 2024)
Technological interventions in the agro-complex sector have experienced rapid development in recent decades, bringing about significant changes in agricultural, livestock, and fisheries practices. This research aims to examine the economic impact of the implementation of modern technology in these three subsectors. Through a systematic review of current scientific literature, this study analyzes various economic aspects affected by technology adoption, including productivity, cost efficiency, product quality, and market competitiveness. Research results show that the use of technologies such as precision farming, automation in animal husbandry, and smart aquaculture have resulted in significant improvements in productivity and efficiency. However, the economic impact varies depending on the scale of operations, the type of technology adopted, and the local socio-economic context. In the agricultural sector, technologies such as soil sensors and drones for crop monitoring have increased crop yields by up to 20% and reduced input use by up to 15%. In animal husbandry, IoT-based livestock health monitoring systems have reduced animal mortality rates by 30% and increased milk production by up to 10%. Meanwhile, in the fisheries sector, the use of automatic feeding technology and real-time water quality monitoring has increased fish survival rates by up to 25% and accelerated production cycles. However, the study also identified economic challenges in technology adoption, including high initial investment costs, the need for new technical skills, and potential dependence on technology suppliers. The research concludes that although technological interventions offer great potential for economic growth in agro-complexes, a careful and tailored approach to the local context is needed to maximize economic benefits while minimizing risks and inequalities.